2022
DOI: 10.3389/fnmol.2022.930941
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Strategies for Understanding the Pathophysiology of Autism Spectrum Disorder

Abstract: Recent breakthroughs in sequencing technology and technological developments have made it easier to analyze the entire human genome than ever before. In addition to disease-specific genetic mutations and chromosomal aberrations, epigenetic alterations in individuals can also be analyzed using genomics. Autism spectrum disorder (ASD) is a neurodevelopmental disorder (NDD) caused by genetic and/or environmental factors. More than a thousand genes associated with ASD have been identified which are known to be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Recently, the heterogeneity of ASD was confirmed in a large study by Kuo et al [38] . However, genetic ASD research continues as if the role of genes in ASD is causal and not contributive [39] . Indeed, MTHFR C667T is the only variant that has been found to indicate genetic vulnerability for ASD diagnosis.…”
Section: The Chronic Dynamic Systemic Encephalopathy Frameworkmentioning
confidence: 99%
“…Recently, the heterogeneity of ASD was confirmed in a large study by Kuo et al [38] . However, genetic ASD research continues as if the role of genes in ASD is causal and not contributive [39] . Indeed, MTHFR C667T is the only variant that has been found to indicate genetic vulnerability for ASD diagnosis.…”
Section: The Chronic Dynamic Systemic Encephalopathy Frameworkmentioning
confidence: 99%
“…To date, more than 1000 genes have been associated with ASD (https://gene.sfari.org (accessed on 13 December 2022)) [10][11][12]. ASD-associated genes are involved in various processes of fetal brain development, in particular neuronal differentiation, migration, and synaptogenesis [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 1000 genes have been associated with ASD (https://gene.sfari.org (accessed on 13 December 2022)) [10][11][12]. ASD-associated genes are involved in various processes of fetal brain development, in particular neuronal differentiation, migration, and synaptogenesis [10,13]. For instance, one of the most frequently reported ASD genes, SHANK3, is a multidomain scaffold protein involved in the regulation of the structural organization of dendritic spines [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sociality and brain development are closely related (Fig. 1 ), and brain developmental disorders during the prenatal period increase the risk of postnatal neurodevelopmental and psychiatric disorders (Usui et al 2023 ; Li et al 2023 ; Doi et al 2022a , b ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…For example, the orbitofrontal cortex, anterior cingulate cortex, and amygdala mirror neuron regions have been reported to be responsible for social interaction, while the inferior frontal gyrus, superior temporal sulcus, and basal ganglia are responsible for communication (Amaral et al 2008 ; Hadjikhani et al 2006 ). Moreover, studies using animals with modifications in genes responsible for ASD have reported developmental abnormalities in various brain regions involved in social behavior (de la Torre-Ubieta et al 2016 ; Wang et al 2014 ; Tebbenkamp et al 2014 ; Doi et al 2022a , b ; Quesnel-Vallières et al 2019 ; Willsey et al 2022 ). Many genes related to human genetic risks associated with brain development and disorders, such as ASD and schizophrenia (SCZ), have been identified to understand the molecular mechanisms underlying social behavior (Doi et al 2022a , b ; Doan et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%